Using a worst pain intensity measure in children and adolescents. (27th February 2017) - Avian, Alexander; Messerer, Brigitte; Meissner, Winfried; Sandner‐Kiesling, Andreas; Kammel, Julian; Labugger, Marlies; Weinberg, Annelie; Berghold, Andrea
Abstract: Aims: To explore inconsistencies and the reliability in worst pain intensity ratings in children. Background: Asking for worst pain always requires a retrospective evaluation which is controversially discussed. Design: Retrospective analysis of registry data and a prospective study. Methods: Retrospective study: 5970 patients [age: 10·2(4·0) years, female: 41% data collection: 2008–2015]; Prospective study: 240 patients [age: 14·7(1·9) years, female: 43%, data collection 2013–2014] were included. In both studies, the number of implausible pain intensity ratings was calculated (both studies: worst pain lower than movement pain or pain at rest, prospective study: number of patients reporting lower pain intensity ratings in worst pain items for the same time period in a second assessment). Test–retest reliability was calculated for the prospective study. Changes in worst pain ratings were analyzed using Wilcoxon signed ranks test. Results: Test–retest reliability ranged from ρ = 0·77–0·90. In the retrospective study, 8·9% (95%CI: 8·2–9·6%) of our patients reported higher movement and/or pain at rest compared with worst pain. In the prospective study, 35·8% (95%CI: 30·0–42·1%) reported higher activity pain ratings compared with worst pain ratings in at least one pain assessment; 13·8% of the pediatric patients reported lower pain intensity ratings in worst pain items in a second assessment compared with the first assessment. Conclusion: Nine to 36% of our patients showed inconsistent worst pain ratings. To overcome this problem, more specific pain intensity items, more than one item or a better instruction for pediatric patients could be used.